close
Blogtrottr
Yahoo!奇摩知識+ - 分類問答 - 科學常識 - 已解決
Yahoo!奇摩知識+ - 分類問答 - 科學常識 - 已解決 
Are you an App Developer?

Win $45,000 by publishing your iOS or Android App! Visit Chupamobile.com
From our sponsors
求工程數學解
Dec 30th 2013, 17:45

1.Total differential vanishes.

Ans:

Ellipsoid: z^2=(4-x^2-y^2+xy)/2

Distance from O(0,0,0) to P(x,y,z):

F(x,y)=√(x^2+y^2+z^2)

=√[(2x^2+2y^2+4-x^2-y^2+xy)/2]

=√[(4+x^2+y^2+xy)/2]

Fx=(2x+y)/√[2(4+x^2+y^2+xy)]=0 => 2x+y=0

Fy=(x+2y)/√[2(4+x^2+y^2+xy)]=0 => x+2y=0

The both equations: x=y=0

Thus z^2=(4-x^2-y^2+xy)/2=2 => z=+-√2

Fxx=Fyy=2>0 => min

So P(x,y,z)=(0,0,+-√2).....ans


2.Lagrange multipliers.

Ans: L=Lamda

F(x,y,z)=√(x^2+y^2+z^2)+L*(x^2-xy+y^2+2z^2-4)

Fx=x/√(x^2+y^2+z^2)+(2x-y)*L=0

Fy=y/√(x^2+y^2+z^2)+(2y-x)*L=0

Fz=z/√(x^2+y^2+z^2)+4z*L=0

Partial(F)/Partial(L)=x^2-xy+y^2+2z^2-4=0

The former 3 equations:

L*√(x^2+y^2+z^2)=x/(y-2x)=y/(x-y)=-1/4

=> 2x+y=x+2y=0 => x=y=0

The last equation: x^2-xy+y^2+2z^2-4=0 => z=+-√2

So P(x,y,z)=(0,0,+-√2).....ans


This entry passed through the Full-Text RSS service — if this is your content and you're reading it on someone else's site, please read the FAQ at fivefilters.org/content-only/faq.php#publishers.

You are receiving this email because you subscribed to this feed at blogtrottr.com.

If you no longer wish to receive these emails, you can unsubscribe from this feed, or manage all your subscriptions
arrow
arrow
    全站熱搜
    創作者介紹
    創作者 jmuko103 的頭像
    jmuko103

    2016台北年菜推薦 年菜食譜 , 年菜預購 , 年菜2015 , 年菜訂購 , 7 eleven年菜訂購 , 年菜宅配 , 年菜菜單 , 年菜推薦 , 年菜食譜大全 , 年菜2016 , 年菜外帶 , 外帶年菜 台中

    jmuko103 發表在 痞客邦 留言(0) 人氣()